Shear Bond Strength of Two Repair Systems to Zirconia Ceramic by Different Surface Treatments: Zirconia repairing systems - A Abdulla, Mohammed; H Hasan, Radhwan (Journal of Lasers in Medical Sciences, 2022)
Introduction: Intraoral repair has been recommended as an option of treatment to repair the chipping or fracture of the veneered zirconia; the success of the procedure mainly determined by the adhesion between the composite resin and zirconia; The present study aimed to investigate the shear bond strength (SBS) of zirconia ceramic treated by a laser and air abrasion and repaired using different intraoral repair systems. Methods: Ninety tube- shaped samples (diameter of 10 mm, and 4 mm height) were divided into three main groups: (1) Group I Zirconia 100%, (2) Group II veneer ceramic 100%, and (3) Group III zirconia 50% veneered with veneering ceramic 50%. Each main group was subdivided into three subgroups (n=10) according to the type of repair system and different surface treatments (no surface treatment, Er,Cr:YSGG laser surface treatment, and air abrasion surface treatment). The SBS was employed using a universal testing machine. The mode of failure was observed using a stereomicroscope. Results: Significant differences in the mean SBS values between the different surface treatments (P˂ 0.05) were observed. Tukey’s post hoc test showed that air abrasion surface treatment of veneer ceramic repaired with Ceramic repair N system showed the highest mean value (13.74 MPa) among the different groups, while no surface treatment of zirconia repaired with Cimara repair system showed the lowest mean value (2.84 MPa). The control group (no surface treatment) had the lowest mean value among all the treated groups. Conclusion: The SBS is surface treatment dependent, and a higher SBS is obtained by air abrasion than laser surface treatments. The Ceramic repair N system had a significantly higher SBS in all surface- treated substrates than in the Cimara repair system.